THE MONTERREY INTERNATIONALIZATION BEHAVIOR - Reyes-Simpe, Jaime (APPS Publications, 2022)
The northern Mexican city of Monterrey is well-known for its high economic development, strong industrial network, and for being the based city of a great number of multinationals from Mexico. However, its business culture has been historically developed in an environment with a lack of inside competition, repercuting their internationalization behavior. In this paper, we develop a binary decision model of Foreign Direct Investment based on the behavioral preferences that characterize multinationals of Monterrey. To test its efficiency, we use the internationalization process of the convenience store chain OXXO, finding that there is a preference for greenfield type of investment in markets with lower levels of competition, and brownfield type of investment for markets where is costly the control over the competition. These factors satisfactorily explain the Foreign Direct Investment process of OXXO in Chile and Peru, except for Brazil, in which we suggest the decission was not optimal. Finally, we discuss that our model could be explanatory for other multinationals from Monterrey and cities with similar business culture history.